Three-dimensional analysis and in vivo imaging for sperm release and transport in the murine seminiferous tubule. Issue 1 (23rd May 2022) - Kanazawa, Yuta; Omotehara, Takuya; Nakata, Hiroki; Hirashima, Tsuyoshi; Itoh, Masahiro
Abstract : In Brief: Spermatozoa are released from Sertoli cells and flow in the seminiferous tubule to the rete testis. Our results suggest that the luminal flow in the tubules is repeatedly reversed and that this physical force helps spermatozoa release from the Sertoli cells. Abstract: Spermatozoa released from Sertoli cells must be transported to the epididymis. However, the mechanism of the luminal flow in seminiferous tubules has remained unclear to date. Therefore, in this study, we investigated luminal flow and movements in the seminiferous tubules by three-dimensional analysis and in vivo imaging. Serial 5-μm-thick mouse testicular sections at 50-µm-intervals were prepared and stained by Periodic Acid-Schiff-hematoxylin. After three-dimensional reconstruction of the seminiferous tubules, the localization of the released spermatozoa and the stages observed in the sections were recorded in each reconstructed tubule. Luminal movements in the seminiferous tubules were observed by in vivo imaging using a fluorescent-reporter mouse and two-photon excitation microscopy system. Spermatozoa without contact to the seminiferous epithelium were not accumulated toward the rete testis. Additionally, such spermatozoa were found on their way not only to the most proximal rete testis but also a more distant rete testis from any stage VIII seminiferous epithelia. In vivo imaging demonstrated that the direction of the flagella of spermatozoa attached to the seminiferous epithelium was repeatedly reversed. The epithelium at the inner curve of the seminiferous tubule was shaken more actively and had fewer spermatozoa attached compared with the epithelium at the outer curve. Our results hence suggest that the luminal flow in the seminiferous tubules is repeatedly reversed and that this physical force helps spermatozoa to be released from Sertoli cells.